Frequency of mutations found in children with chronic kidney disease due to steroid-resistant nephrotic syndrome - Loza, Reyner (2023)
Chronic kidney disease in children may be caused by a group of genetic abnormalities of the kidney, urinary tract and hereditary nephropathies. Objective: To report the frequency of mutations in children with steroid-resistant nephrotic syndrome (SRNS). Methods: A multicentric case series among children with SRNS identified through direct sequencing of NPHS1, NPHS2, NPHP1 and WT1 genes. Results: 33 children were enrolled; 45.5% were females; mean age was 13±7 years; 78.8% were mestizo: 24.2% consanguineous; 60.6% were receiving dialysis: 72.7% had SRNS and 8/24 (33.3%) of them presented at least one mutation to WT1, NPHS1, NPHP1 and NPHS2 genes. Corresponding values for these mutations were 37.5% (3/8), 25% (2/8), 25% (2/8) and 12.5% (1/8), respectively. Conclusions: 33% of pediatric patients with SRNS presented gene mutations, the most frequent of these mutations was WT1.